Does Supply or Demand Drive the Credit Cycle? : Evidence from Central, Eastern, and Southeastern Europe - Everaert, Greetje (IMF Working Papers; Working Paper, 2015)
Countries in Central, Eastern, and Southeastern Europe (CESEE) experienced a credit boom-bust cycle in the last decade. This paper analyzes the roles of demand and supply factors in explaining this credit cycle. Our analysis first focuses on a large sample of bank-level data on credit growth for the entire CESEE region. We complement this analysis by five case studies (Latvia, Lithuania, Montenegro, Poland, and Romania). Our results of the panel data analysis indicate that supply factors, on average and relative to demand factors, gained in importance in explaining credit growth in the post-crisis period. In the case studies, we find a similar result for Lithuania and Montenegro, but the other three case studies point to the fact that country experiences were heterogeneous.